THE EFFECTS OF MORNING BRIEFINGS, WORK MOTIVATION, AND FOREMAN LEADERSHIP ON THE WORK PRODUCTIVITY OF PALM OIL (Elaeis guineensis Jacq) HARVESTERS AT PTPN IV’S KWALA SAWIT PLANTATION IN LANGKAT REGENCY - Rafael Faiven Saragih; Kesya Emya Regina Br Pelawi; Steven Rionaldo Sihombing; Alvando Fransiskus Purba; Muhammad Arif Nasution (Agriprimatech, 2026)
Oil palm (Elaeis guineensis Jacq) is a plantation commodity that contributes significantly to the Indonesian economy. In the oil palm plantation industry, harvester productivity is a crucial factor in determining the success of fresh fruit bunch (FFB) production. This productivity is influenced by various human resource factors, including discipline through the implementation of morning roll call, work motivation, and foreman leadership in the field. However, in practice, harvesters are still found to be absent or not arrive on time for the morning roll call, thus potentially affecting the level of work productivity. This study aims to identify the influence of morning roll call, work motivation, and foreman leadership on harvester work productivity. This study was conducted at PTPN IV Kwala Sawit Plantation, Langkat Regency. Sampling was carried out using a purposive sampling method, focusing on harvesters working on oil palm plantations. This study involved a sample of 80 harvest workers. Data were analyzed using a Likert scale and multiple linear regression. The findings of this study show that simultaneously the variables of morning roll call, motivation, work, and foreman leadership have a significant effect on harvester labor productivity. Partially, each of these variables was also proven to have a significant influence on the work productivity of harvesters at PTPN IV Kwala Sawit Plantation.